Mapping United States-Brazil technical cooperation in the early Cold War years: the case of the Joint Brazil-United States Economic Development Commission (1951-1953) - Gomes, Nathalia Candido Stutz (2019)
The purpose of this thesis is to analyze the Joint Brazil-United States Economic Development Commission (JBUSEDC) (1951-1953), a largely unexplored initiative in the literature. The JBUSEDC was an innovative undertaking established under Harry Truman\'s Point (1949-1953) Four Program, functioning during the Getúlio Vargas\' Administration (1951-1954). In the aftermath of the Second World War, poor facilities of Brazilian railways, ports, power, and navigation were the main bottlenecks to the development of the country. In the JBUSEC, Brazilian and American technicians elaborated studies and projects to tackle them. Based on both American and Brazilian primary sources, this research identifies essential features of JBUSEDC\'s activities in the country, namely its institutional organization, proceedings, main challenges, outcomes, and strategic interests involved. JBUSEDC\'s organization was broad and centralized all Point Four activities in the country. Expectations that the World Bank (IBRD) and, to a lesser extent, the U.S. Export-Import Bank (Eximbank) was going to provide the loans necessary to implement JBUSEDC\'s projects increased optimism. However, out of the 41 projects elaborated, only 14 received loans from either institution. This outcome nurtured frustrations among Brazilian policymakers on the prospects of economic cooperation with the U.S. The fact that the IBRD was the first instance lender to Brazilian development projects gave the Bank considerable intervention power. Indeed, the IBRD imposed many conditionalities to provide loans to Brazil. Among them were approving a free-market exchange bill, reforming the administration of State-owned railway system, besides tackling economic unbalances and commercial arrears. This study explores the political, economic, and geostrategic interests underlying the JBUSEDC. Given the escalation of tensions between the U.S. and the Soviet Union when the Korean War began, Washington made efforts to conciliate Brazil\'s infrastructure projects with the possibilities of expanding the supply of strategic raw materials in case the war became global. Besides filling gaps of the existing literature, these findings shed light on other research possibilities about overall Brazil-U.S. technical cooperation, other joint commissions installed throughout the world under the Point Four program and, finally, about relations of the so-called \"Third World countries\" with international financing institutions in the 1950s.